Effects of Buffalo Milk and Cow Milk on Lipid Metabolism in Obese Mice Induced by High Fat - Jiang, Maocheng; Meng, Zitong; Cheng, Zhiqiang; Zhan, Kang; Ma, Xiaoyu; Yang, Tianyu; Huang, Yinghao; Yan, Qi; Gong, Xiaoxiao; Zhao, Guoqi (Frontiers in Nutrition, 2022)
The aim of this study was to evaluate the effects of buffalo milk and cow milk on lipid metabolism in obese mice. Through the milk composition analysis, compared with cow milk, we found that the index of lactose, fat, protein, total solid content from buffalo milk was a significant difference. Through the milk metabolite extraction and LC-MS/MS analysis, the results showed that Linoleic acid metabolism pathways, Pentose and glucuronate interconversions pathways, and metabolism of xenobiotics by cytochrome P450 pathways were significantly different in positive and negative ionization modes. By feeding test, we fed 3 groups of C57BL/6J mice (n = 6 per group) for 5 weeks: (1) High-Fat Diet group(HFD group); (2) High-Fat Diet + Buffalo Milk group(HBM group); (3) High-Fat Diet + Cow Milk group(HCM group). Our results showed that, compared with the HFD group, the HBM and HCM group had significantly decreased body weight in 1-4 weeks; in the fifth week, the weight of mice in the HCM group was also significantly lower than that in the HFD group. Using qRT-PCR, we found that the ACAA2, ACACB and SLC27A5 genes were significantly increased after HCM group intervention for mice with high fat diet induced obesity, but the HBM group did not change. By H&E staining and Oil red O staining on the liver, compared with the HFD group, we found that the adipocyte number, size and lipid accumulation significantly decreased upon HCM group intervention, but the HBM group did not change. Beyond that, we also identify the result from the qRT-PCR point of view. We found that the expression levels of inflammation related genes were significantly increased upon buffalo milk intervention. In conclusion, the results show that cow milk intervention has a beneficial effect on body weight, hepatic adipose tissue lipolysis in obesity mice.